Analysis of Predictors that Influence on Prevalence of Hypertension - Rida Darotin; Eky Madyaning Nastiti (Jurnal Kesehatan dr. Soebandi, 2022)
Introduction: Hypertension is a health problem that has an important role. If not handled properly, it can lead to various complications in the form of damage to target organs and in fatal cases it can lead to heart disease, kidney failure or stroke which often leads to death. The purpose of this study was to analyze predictor factors (which affect the incidence of hypertension: family history, exercise habits, obesity, saturated fat consumption pattern and level of knowledge) on the incidence of hypertension. Methods: This research is descriptive with a retrospective approach. using total sampling technique. The total population is 40 people in Jember. The time of the study was carried out in May 2019 – June 2019. Data collection tools used questionnaires and observation sheets. Statistical analysis using fisher exact test. Result: There is a relationship between the incidence of hypertension with exercise habits (P Value 0.021 analysis using fisher exact test) and level of knowledge (P value 0.003 using Fisher's exact test). There is no relationship between the prevalence of hypertension with family history, obesity and consumption of foods containing fat (P Value 0.305, P Value 0.211, P Value 0.45 using Fisher Exact test). Conclusion: The incidence of hypertension in members of Aisyiyah Glundengan Wuluhan, Jember Regency is related to exercise habits and level of knowledge. Keyword: Exercise habits, Hypertension, Level of knowledge, Obesity